Resurrection and typification of Verbascum auriculatum (Scrophulariaceae), a long-disused name in Flora Graeca Sibthorpiana - Zografidis, Aris (Phytotaxa, 2018)
Verbascum auriculatum, a name for a species discovered during Sibthorp’s first expedition in the Eastern Mediterranean, had long been sunk into synonymy of V. mucronatum. Surprisingly, however, the original material of this name was found not to match V. mucronatum but V. propontideum, a very distinct species, remarkably dissimilar to V. mucronatum. V. auriculatum is lectotypified and resurrected since V. propontideum represents a younger synonym. The species is endemic to the S.E. Aegean region, whereas Sibthorp has left no indication of where and when he collected the plant. A hypothesis on the possible locus classicus and date of the original collection is presented.